On the ‘cusp’ of clinical feasibility: aortic wall shear stress derived non-invasively with 4D flow MRI - Bollache, Emilie; Fedak, Paul W. M.; Markl, Michael; Barker, Alex J. (Journal of Thoracic Disease, 2019)
It is with great interest that we read the expert commentary by Carelli et al. regarding our recent study in their Editorial entitled “Is wall shear stress ready to become a prime-time clinical tool?—measurement of post-surgical patterns in patients undergoing aortic valve and thoracic aortic replacement using 4-dimensional flow magnetic resonance imaging” (1). We agree with the authors that basic wall shear stress (WSS) measurements are on the cusp of clinical feasibility. We also agree that additional technical developments remain to occur in order to enable more sophisticated, time-resolved WSS measurements—and we continue to work diligently to make these available to the wider community.